Praktikalitas Pengembangan Media Menggunakan Aplikasi Articulate Storyline 3 Pada Pembelajaran Matematika di Sekolah Dasar - Kosandi, Dzaky; Masniladevi, Masniladevi (Universitas Negeri Padang, 2024)
This research aims to develop learning media based on the Articulate Storyline 3 application on rectangular material in class IV Elementary School. The type of research used is R&D (Research and Development) used the ADDIE development model, Analysis, Design, Development, Implementation, and Evaluation. The research subjects were carried out at SD Negeri 10 Bandar Buat. The validity and practicality test instrument is carried out in the form of filling out a questionnaire and carrying out an analysis of the needs of teachers, students and curriculum. The learning media that has been designed will be validated learning media with validators including material, language and media experts by providing validity questionnaires to the validator experts. Validity of the development of Articulate Storyline 3 learning media, the results were 91,6% (very valid), for material experts, 95% (very valid) for linguists 95,8% (very valid) for expert media. Practicality in schools is very practical with a percentage of teacher responses of 91,6% and student responses of 92%. So it can be concluded that the development of learning media based on the Articulate Storyline 3 application in mathematics learning in elementary schools has been tested for validity and can be used in the learning process.